Connections, contracts and sanctions informal commercial contracting among Chinese in Metro Manila - Clemente, Tina S. (Asian Studies, 2015)
Do Chinese merchants in contemporary Philippines still practice personalistic engagement in business? As a primarily descriptive study, we focus on the Chinese in Metro Manila and look at features of informal contracting as premised in personalistic ties among Chinese involved in business. Operationalizing a qualitative investigation, we utilize survey research as well as in-depth key-informant interviews and attempt to explore informal contracting through the nuances that include the types of business connections, reasons for engaging in informal contracts, use and dominance of contract types, factors that deter contract violations and sanctions against connections who violate informal agreements.